2014
DOI: 10.1002/jcp.24787
|View full text |Cite
|
Sign up to set email alerts
|

Pin1 Plays a Critical Role as a Molecular Switch in Canonical BMP Signaling

Abstract: Pin1 is a peptidyl prolyl cis-trans isomerase that specifically binds to the phosphoserine-proline or phosphothreonine-proline motifs of numerous proteins. Previously, we reported that Pin1 deficiency resulted in defects in osteoblast differentiation during early bone development. In this study, we found that adult Pin1-deficient mice developed osteoporotic phenotypes compared to age-matched controls. Since BMP2 stored in the bone matrix plays a critical role in adult bone maintenance, we suspected that BMP R-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 59 publications
0
33
0
Order By: Relevance
“…Genetic studies have shown that LRP5 can control bone mass (8,9), and conditional deletion of ␤-catenin in the embryonic limb and head mesenchyme results in the absence of mature osteoblasts in membranous bones (10,11). Our previous studies have shown the importance of Pin1 in bone development (25,26,30). Considering this, Wnt signaling, including all components of the canonical pathway, and Pin1 are deemed essential for bone formation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Genetic studies have shown that LRP5 can control bone mass (8,9), and conditional deletion of ␤-catenin in the embryonic limb and head mesenchyme results in the absence of mature osteoblasts in membranous bones (10,11). Our previous studies have shown the importance of Pin1 in bone development (25,26,30). Considering this, Wnt signaling, including all components of the canonical pathway, and Pin1 are deemed essential for bone formation.…”
Section: Discussionmentioning
confidence: 95%
“…Immunofluorescence and Immunohistochemistry-The detection of Pin1 and ␤-catenin by immunofluorescence and immunohistochemistry was performed as described previously (28,30).…”
Section: Methodsmentioning
confidence: 99%
“…This balance between the cis and trans forms of the substrate has been proposed to be critical for Pin1‐mediated regulation of biological processes (Yaffe et al, ) (Fig. ), including bone cell differentiation (Yoon et al, ; Islam et al, ; Yoon et al, ). Pin1 also exerts an additional level of control after phosphorylation in the cascade of post‐translational events.…”
Section: Pin1 Substrates That Are Also Critical Modulators In Bone Cellsmentioning
confidence: 99%
“…Smad2/3 was the first target of Pin1 identified to have a role in TGF‐β signaling (Nakano et al, ; Matsuura et al, ; Aragon et al, ; Shen et al, ). More recently, the TGF‐β subfamily ligand BMP (bone morphogenetic protein), which transmits signals in the canonical pathway through Smad1/5, was shown to be controlled by Pin1 (Shen et al, ; Yoon et al, ). Furthermore, Pin1‐mediated stabilization of Smad1/5 resulted in accelerated osteoblast differentiation and bone mineralization (Fig.…”
Section: Role Of Pin1 In Osteoblast Cell Signalingmentioning
confidence: 99%
See 1 more Smart Citation